Optimal central frequency for non-contact vital sign detection using monocycle uwb radar - Rittiplang, Artit; Phasukkit, Pattarapong; Orankitanun, Teerapong (My University, 2020)
Ultra-wideband (UWB) radar has become a critical remote-sensing tool for non-contact vital sign detection such as emergency rescues, securities, and biomedicines. Theoretically, the magnitude of the received reflected signal is dependent on the central frequency of mono-pulse waveform used as the transmitted signal. The research is based on the hypothesis that the stronger the received reflected signals, the greater the detectability of life signals. In this paper, we derive a new formula to compute the optimal central frequency to obtain as maximum received reflect signal as possible over the frequency up to the lower range of Ka-band. The proposed formula can be applicable in the optimization of hardware for UWB life detection and non-contact monitoring of vital signs. Furthermore, the vital sign detection results obtained by the UWB radar over a range of central frequency have been compared to those of the former continuous (CW) radar to provide additional information regarding the advantages and disadvantages of each radar.
Keywords: Bessel-Gaussian integral; Hankel Transform; Monocycle pulse; Non-contact vital sign detection; Optimal frequency; UWB radar